Ceramic Fibers Reinforced Functionally Graded Thermal Barrier Coatings. Issue 8 (23rd June 2017) - Wang, Chang; Cui, Xiufang; Jin, Guo; Gao, Zonghong; Jin, Jiannong; Cai, Zhaobing; Fang, Yongchao
Abstract : The long‐term durability is a considerable challenge for the use of thermal barrier coatings (TBCs). In order to solve this problem, introduction of yttria‐stabilized zirconia (YSZ) short fibers in functionally graded system is employed to strengthen the durability of TBCs. Four coatings are deposited on In738LC substrate by atmospheric plasma spray (APS). Thermal cycling behaviors and fiber toughening mechanisms of coatings are systematically studied. Result shows that the thermal cycling lifetime of graded TBCs with the addition of fibers can reach 406 ± 21 at 850 °C, which increases by 60% compared to that of typical APS YSZ TBCs. Moreover, the improvement of lifetime mainly attributes to the fiber breakage, the fiber‐matrix interface debonding, and the crack deflection. Abstract : In this study, a novel method, namely, introduction of yttria‐stabilized zirconia (YSZ) short fibers in functionally graded system, is used to solve the long‐term durability of TBCs. Thermal cycling lifetime of this TBC is improved greatly. The improvement is mainly attributed to the fiber breakage, the fiber‐matrix interface debonding, and the crack deflection.